Measuring The Importance And Efficiency Of Research And Development Expenditures In The Transformation Of Knowledge-based Economies: A Case Study Of The Asean Region - Ibne Afzal, Munshi Naser; Lawrey, Roger
This paper presents an evaluation of the efficient use of public research and development (R&D) expenditure in the ASEAN (Association of Southeast Asian Nations) region by using Data Envelopment Analysis (DEA). The efficiency of public R&D expenditure is measured as a percentage of GDP, by considering it as an input to knowledge generation. Two knowledge outputs are considered, namely real GDP growth and high-tech goods export as a percentage of total manufacturing exports. All data are collected from World Development Indicators (2010), World Competitiveness Yearbook (2011) and ASEAN publications. The efficiency results are prepared following both constant returns to scale (CRS) and variable returns to scale (VRS) assumptions. The efficiency scores under CRS suggest that the Philippines and Indonesia were the best performers in 2010 while under VRS, Singapore and Thailand were the most efficient countries in 2010. Special emphasis is placed on how to present the DEA results to government and policy makers in order to provide more policy guidance on how to achieve optimum knowledge output relative to R&D expenditure.